The Modernity Dilemma of Life Education and the Path Analysis - Bin, Xue (Journal of Theory and Practice of Contemporary Education, 2023)
Starting from the modern dilemma in the development of life education in mainland China, we focus on practicing the educational concept of transforming people with love, promoting the synergy of home, school and society to construct positive forces, and drawing on the strengths of life education in the West and Taiwan to explore a development path of life education suitable for China's national conditions, so as to help young people establish correct life values, promote their understanding of life, and lay the foundation for a happy and complete life in the future.